Faktor Risiko Terkait Manajemen Kesehatan Unggas terhadap Infeksi Virus Flu Burung di Tempat Penampungan Ayam (THE RISK FACTOR OF POULTRY HEALTH MANAGEMENT TO THE INFECTION OF AVIAN INFLUENZA VIRUS IN POULTRY COLLECTING FACILITIES) - Basri, Chaerul; ., Zudanang; ., Sunandar; Sudarnika, Etih (Jurnal Veteriner, 2013)
The aim of the study was to determine the association between the implementation of poultryhealth management and the spread of avian influenza virus in Poultry Collecting Facilities (PCFs).  Thestudy was performed by maintaining 7-8 sentinel chickens in 39 PCFs in Jakarta for three months.  Thevariables evaluated for poultry health management were health certificate, health inspection, healthinspector, health inspection method, and handling of sick and dead birds. Data on the variables werecollected by interview with supervisor of PCFs.  The AIV infection were detected by rt-PCR from the cloacaland tracheal swab of the dead birds with.  The results showed that the methodes of handling of sick birdswere significantly associated with infection of AIV (RR=2,00 ; 95% CI  = 1,31-3,05).  The other variables didnot show significance association.  The risk of AIV infection was twice higher  the sick keeping side birdsalive, or by separating, or treating the birds in the same cage than by slaughtering them. Poultry healthmanagement in PCFs need to be improved in order to prevent and control the spreading of AIV in Indonesia.
Keywords: avian influenza, health management, poultry collecting facilities (PCFs), chicken